2021
DOI: 10.2174/1573397117666210902151130
|View full text |Cite
|
Sign up to set email alerts
|

Lymphadenopathy as a Prodrome for Systemic Lupus Erythematous

Abstract: : A 41-year-old woman presented to the hospital with one month of fever, chills, lymphadenopathy, abdominal pain, a bilateral upper extremity rash, and malaise. The patient had no significant prior medical history and was physically active, kickboxing twice a week and working 16-hour days. She reported increased difficulty getting out of bed over the span of one month. Physical exam was notable for tender, palpable posterior cervical lymph nodes that were mobile and about 1 cm in maximum diameter. There was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…La linfadenopatía por LES tiene una incidencia estimada del 1% al momento del diagnóstico 8 , no obstante, ocurre hasta en el 25 % de los pacientes con LES en algún momento de la enfermedad. Típicamente las adenopatías son blandas, indoloras, varían en tamaño de 0,5 cm a varios centímetros y se detectan generalmente en áreas cervical, axilar e inguinal y plantean problemas en el diagnóstico, así como la necesidad de descartar otras enfermedades que pueden manifestarse con linfadenopatías 9 .…”
Section: Discussionunclassified
“…La linfadenopatía por LES tiene una incidencia estimada del 1% al momento del diagnóstico 8 , no obstante, ocurre hasta en el 25 % de los pacientes con LES en algún momento de la enfermedad. Típicamente las adenopatías son blandas, indoloras, varían en tamaño de 0,5 cm a varios centímetros y se detectan generalmente en áreas cervical, axilar e inguinal y plantean problemas en el diagnóstico, así como la necesidad de descartar otras enfermedades que pueden manifestarse con linfadenopatías 9 .…”
Section: Discussionunclassified
“…Obwohl Lymphadenopathien beim SLE in 33-69 % beobachtet werden [17,21], haben sie aufgrund ihrer fehlenden Spezifität keinen Eingang in die EULAR Klassifikationskriterien gefunden. Sie können als Prodromi eines SLE vorhanden sein [22], treten aber meist generalisiert und bei jüngeren Patienten bei aktiver Erkrankung auf. Sie sind assoziiert mit einer Hautbeteiligung, Hepatosplenomegalie, hohen ds-DNA Antikörpertitern und Komplementverbrauch [21].…”
Section: Systemischer Lupus Erythematodes (Sle)unclassified
“…In systemic lupus erythematosus (SLE), LAP represents a benign and common finding. Though it is not considered a clinical criterion in the 2019 European League Against Rheumatism/American College of Rheumatology (EULAR/ACR) classification criteria, some reports have suggested that it can be the first manifestation, with a cumulative incidence ranging from one-third to one-half of the cases [2,3,4,5]. There are some clinical and paraclinical characteristics associated with LAP in SLE, such as more constitutional symptoms (fatigue, fever, and weight loss), more cutaneous symptoms, increased anti-dsDNA antibodies, and decreased complement levels [6,7].…”
Section: Introductionmentioning
confidence: 99%